Biosynthesis and Kinetics of Silver Nanoparticles Formation by Reduction using Banana Kepok (Musa balbisiana) Peel Extract - Rangga, Wara Dyah Pita; Setiawan, Dhimas; Khosiatun, Khosiatun (ASEAN Journal of Chemical Engineering, 2017)
Biosynthesis and silver nanoparticles formation during the reduction of AgNO3 were carried out by using an aqueous peel extract of banana kepok (Musa balbisiana) as a stabilizing agent. The formation of the stable silver nanoparticles with different concentration of AgNO3 has resulted in mostly spherical particles. The Ultraviolet-Visible spectrophotometer, Transmission Electron Microscopy, X-Ray Diffractometer were used to characterize these biosynthesized silver nanoparticles. The spherical shaped nanoparticles were uniformly distributed with the range diameter of 5 to 50 nm and the particles were naturally crystallized with the crystal structure of the face-centered cubic geometry. Additionally, the kinetics of the formation process of silver nanoparticles was observed by the UV-Vis spectrophotometer. Based on the kinetic functions, the reduction process of banana peel extract had a constant formation rate of the autocatalytic process at 4.35 x 10-4 /s.